The Decision Support System of the selection of tourist attractions of Bali Island is used Preference method of Organization For Enrichment Evaluation - Eva Zuraidah (Universitas Islam Sultan Agung, 2020)
Tourism today is very potential to be developed as one source of local revenue by providing information both online and offline and online for the community so that increased regional revenue desired by the government. The number of tourist attractions in Bali to make many tourists from abroad and in the country feel confusion in determining the destination, the most beautiful and easy to reach the place. There are many criteria to be considered, then through this recommender system, tourists can find out what tours they will visit while in Bali. One of the problems of decision making with many criteria and attributes in choosing a tourist attraction is to provide detailed decisions that refer to the weight scale they have. The decision support system gives priority result of tourist attraction suitable for every tourist from abroad and in the country. This research is focused on applying multi-attribute decision making, for decision support system using the preferred method of organization for enrichment evaluation. This research uses the descriptive analytical method to present a summary of survey results made by spreading quizzers to domestic, foreign and foreign tourists, from tourists who want to choose the island of Bali tourism in accordance with cost, security, natural beauty, facilities and infrastructure and location the island of Bali